Diverse phosphorylation patterns of B cell receptor-associated signaling in naïve and memory human B cells revealed by phosphoflow, a powerful technique to study signaling at the single cell level - Toapanta, Franklin R.; Bernal, Paula J.; Sztein, Marcelo B. (Frontiers in Cellular and Infection Microbiology, 2012)
Following interaction with cognate antigens, B cells undergo cell activation, proliferation and differentiation. Ligation of the B cell receptor (BCR) leads to the phosphorylation of BCR-associated signaling proteins within minutes of antigen binding, a process with profound consequences for the fate of the cells and development of effector immunity. Phosphoflow allows a rapid evaluation of various signaling pathways in complex heterogenous cell subsets. This novel technique was used in combination with multi-chromatic flow cytometry and fluorescent-cell barcoding to study phosphorylation of BCR-associated signaling pathways in naïve and memory human B cell subsets. Proteins of the initiation (Syk), propagation (Btk, Akt) and integration (p38MAPK and Erk1/2) signaling units were studied. Switched memory (Sm) CD27+ and Sm CD27- phosphorylation patterns were similar when stimulated with anti-IgA or -IgG. In contrast, naïve and unswitched memory (Um) cells showed significant differences following IgM stimulation. Enhanced phosphorylation of Syk was observed in Um cells, suggesting a lower activation threshold. This is likely the result of higher amounts of IgM on the cell surface, higher pan-Syk levels and enhanced susceptibility to phosphatase inhibition. All other signaling proteins evaluated also showed some degree of enhanced phosphorylation in Um cells. Furthermore, both the PLC-γ2 and PI3K pathways were activated in Um cells, while only the PI3K pathway was activated on naïve cells. Um cells were the only ones that activated signaling pathways when stimulated with fluorescently-labeled S. Typhi and S. pneumoniae. Finally, simultaneous evaluation of signaling proteins at the single cell level (multi-phosphorylated cells) revealed that interaction with gram positive and negative bacteria resulted in complex and diverse signaling patterns. Phosphoflow holds great potential to accelerate vaccine development by identifying signaling profiles in good/poor responders.